The Role of International Human Rights Norms in Combating Discrimination and Promoting Equality - Irsyad Dhahri (Eastasouth Institute, 2023)
This research explores the role of international human rights norms in combating discrimination and promoting equality in Indonesia. This paper examines the influence of international human rights norms on legal and policy reform, the implementation of these norms in addressing discrimination, and their overall effectiveness in the Indonesian context. Its theoretical framework includes an intersectionality approach to discrimination and recognizes the social construction of discriminatory practices. The study used a mixed methods approach, including literature review, legal framework analysis, and case studies, to provide a comprehensive analysis. Its findings show significant alignment between international human rights norms and Indonesia's legal framework. However, there are still challenges in its implementation due to limited awareness, cultural barriers, weak institutional capacity, and regional variations. The study concludes by emphasizing the importance of raising awareness, overcoming cultural barriers, and strengthening institutional capacity to strengthen the role of international human rights norms in combating discrimination and promoting equality in Indonesia.